Towards North American monetary union? : the politics and history of Canada's exchange rate regime - Helleiner, Eric, 1963- (McGill-Queen's University Press, 2006)
"Eric Helleiner provides a detailed exploration of the politics underlying Canada's recent debate over the merits of monetary union with the United States. Comparing the US Federal Reserve and the European Monetary Union, he argues that Canada would exercise far less influence within a North American monetary union than individual countries do within the European community. He also analyses the seemingly paradoxical support of Quebec sovereignists for free trade and monetary union."--Jacket